2005
DOI: 10.1093/humrep/dei243
|View full text |Cite
|
Sign up to set email alerts
|

Similar endometrial development in oocyte donors treated with either high- or standard-dose GnRH antagonist compared to treatment with a GnRH agonist or in natural cycles

Abstract: No relevant alteration was observed in the endometrial development in the early and mid-luteal phases in women undergoing controlled ovarian stimulation for oocyte donation following daily treatment with a standard- or high-dose GnRH antagonist. In addition, the endometrial development after GnRH antagonist mimics the natural endometrium more closely than after GnRH agonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(69 citation statements)
references
References 26 publications
4
60
1
3
Order By: Relevance
“…In this regard, a recent meta analysis comparing outcomes between antagonist and agonist cycles, including 13 randomized clinical trials with a range of 2-101 pregnant cases for each study, miscarriage rates were not found to be different (11.7% vs 11.5%) [18]. However, the studies in this meta analysis in the Cochrane review did not take into account the plurality of gestations and the definitions of miscarriage were not uniform [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Short Communicationmentioning
confidence: 84%
See 1 more Smart Citation
“…In this regard, a recent meta analysis comparing outcomes between antagonist and agonist cycles, including 13 randomized clinical trials with a range of 2-101 pregnant cases for each study, miscarriage rates were not found to be different (11.7% vs 11.5%) [18]. However, the studies in this meta analysis in the Cochrane review did not take into account the plurality of gestations and the definitions of miscarriage were not uniform [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Short Communicationmentioning
confidence: 84%
“…Initial randomized clinical trial (RCT) declared that neither implantation nor pregnancy rates were significantly different than agonist protocol; however, subsequent meta analysis reported inferior pregnancy rates among patients using GnRH antagonist [2][3][4][5]. Furthermore, some studies assessed ovarian compartment during stimulation with GnRH agonists and antagonists, as measured by expressions of hormones and paracrine growth factors, and none of them found significant differences in clinical outcome [6][7][8]. In order to determine whether this subtle clinical outcome difference between those GnRH analogues could be integral to endometrial microenvironment, some studies addressed endometrium as a confounding factor.…”
Section: Short Communicationmentioning
confidence: 99%
“…Tarlatzis и соавторы предполагали, что применение ант-ГнРГ может оказывать более негативное влияние на эндометрий по сравнению с а-ГнРГ [29]. Но в то же время другие исследователи показали, что эндометрий в прото-коле с ант-ГнРГ больше соответствует натуральному циклу, чем в протоколе а-ГнРГ [30]. Так, А. Tavaniotou и коллеги проиллюстрировали, что применение а-ГнРГ в «длинном» протоколе приводит к глубокой десенситизации гипофиза [16].…”
Section: индукторы влияющие на эндометрий в стимулированных циклахunclassified
“…In a molecular level embryo implantation is a dialog between blastocyst and receptive endometrium which is mediated by various growth factors, cytokines, lipid mediators, transcription factors and other putative molecules often regulated by steroid hormones. In recent years, numerous studies applying global gene expression analysis have found a wide range of genes up-or down regulated in human endometrium during the IW (Carson et al, 2002;Riesewijk et al, 2003;Horcajadas et al, 2004;Krikun et al, 2005;Mirkin et al, 2005;Simon et al, 2005;Punyadeera et al, 2005;Talbi et al, 2006;Haouzi et al, 2009a,b;Altmäe et al, 2010). Each study has brought out candidate genes believed to be crucial in embryo implantation process but the overlap of potential marker genes between different publications has still remained relatively low.…”
Section: Endometrial Gene Expression During the Time Of Embryo Implanmentioning
confidence: 99%